Frumixo - Thussin, Azrie Azhar; John, Braker Bradley; Eduan, Mohd Syafiz; Razali, Mohd Ikhwan; Bukarak, Mariana (2016)
Frumixo is a business plan of a bar cafe of serving fresh healthy infuse water in Malaysia. The demand of our product will good and it will be the first of kind business in Malaysia. Many of other ventures also serve fresh juice but our product is healthier and different from fresh juice of others because we use 100 per cent fresh fruit, no adding sugar and natural flavour without preservation. The company name as Frumixo because of fresh fruit that infuse with water and the taste of delicious that naturally comes from the flavour of the fruit. Our product can act as a supplement that can be bought cheaply and no side effect and also serve to all people especially to student, office worker and people who go to fitness centre and it comes with various benefits that can help the individual to stay healthy. For Example it can help digestion problem, help reducing body weight and more. We will see our business will expand to other branch around Malaysia.